Effects of dietary hemp co-product inclusion on laying hens performances and on egg nutritional and functional profile - D. Lanzoni; M. Skřivan; M. Englmaierová; E. Petrosillo; L. Marchetti; V. Skřivanová; V. Bontempo; R. Rebucci; A. Baldi; C. Giromini (Italian Journal of Animal Science)
The European Union promotes a circular economy by valorising food industry scraps as co-products for animal feed. Hemp (Cannabis sativa L.) co-products are promising for their nutritional and functional profile, but their use in animal nutrition remains limited. This study evaluated the effect of increasing levels (0%, 3%, 6%, 9%) of a hemp co-product (variety Futura) from hempseed cleaning, included in laying hens’ diets (control, T3, T6, T9), on performance and the nutritional/functional quality of egg yolks, focusing on total phenolic content (TPC) and antioxidant activity (FRAP and ABTS assays), also assessed after green chemical extraction and in vitro digestion. Including up to 9% hemp co-product in diets did not affect dry matter and protein digestibility but improved the functional profile. A 9% inclusion significantly increased egg mass production (p < 0.01) and reduced saturated fatty acid content (T9: 7672 mg/100 g; T6: 8534 mg/100 g; T3: 8837 mg/100 g; control: 8742 mg/100 g), alongside an improved n-6/n-3 fatty acid ratio. Cholesterol levels were significantly lower than the control in all concentrations tested, with better results for T9 (p < 0.01). Antioxidant activity, measured via ABTS after in vitro digestion, increased significantly (control: 601.12 ± 42.40 mg TE/100 g; T3: 773.17 ± 43.77 mg TE/100 g; T6: 765.64 ± 38.71 mg TE/100 g; T9: 843.48 ± 38.71 mg TE/100 g; p < 0.05), despite no differences in TPC. In conclusion, the inclusion of 9% hemp co-product in laying hens’ diets improved egg production and yolk quality, highlighting its potential for animal feed. However, the composition variability requires further evaluation to ensure future large-scale application.